Integrated cytological and transcriptomic analysis reveals insights into pollen fertility in newly synthetic Brassica allohexaploids - Tian, Zhaoran; Ji, Chengyan; Xie, Zhengqing; Shi, Xinjie; Tian, Baoming; Cao, Gangqiang; Wei, Xiaochun; Yang, Yan; Wei, Fang; Shi, Gongyao (Frontiers in Plant Science, 2023)
Trigenomic Brassica allohexaploids (AABBCC, 2n = 6x = 54) have great potential in oilseed breeding and genetic diversity. However, Brassica allohexaploids do not exist naturally, and the underlying mechanism regulating pollen fertility in artificially synthesized Brassica allohexaploids is still unclear. In this study, synthetic Brassica allohexaploids were produced by crossing allotetraploid B. carinata (BBCC, 2n = 4x = 34) and diploid B. rapa (AA, 2n = 2x = 20), followed by chromosome doubling. The results showed that the pollen fertility was significantly reduced and the pollen structures were mostly distorted, but the nursing anther tapetum developed normally in the synthetic Brassica allohexaploids. Furthermore, the data showed that the meiotic events occurred irregularly with uneven chromosome segregation and microspore development appeared mostly abnormal. Transcription analysis showed that the genes involved in beta-tubulin binding and chromosome segregation, and pollen formation were largely downregulated, which might play an essential role in reduction of pollen fertility in the Brassica allohexaploids. In conclusion, this study elucidated the related mechanisms affecting pollen fertility during male gametophytic development at the cytological and transcriptomic levels in the newly synthesized Brassica allohexaploids.